Export Market Diversification and Export Performance of Sri Lanka: A Cointegration Analysis - Bhavan , T (Asian Journal of Empirical Research, 2017)
This paper aims to investigate the existence of geographical export market diversification and its relations with export performance of Sri Lanka. The paper identifies the existence of geographical export market diversification by using Herfindahl Index, and empirically investigates the long run and the short run relationship between market diversification and export performance. The time series data extracted from the World Bank database are used to construct Index and appropriate variables. Johansen’s co-integration analysis was performed to investigate the relationships between export market diversification over a period 1999 to 2015. The trend of the Herfindhal Index reveals that market diversification exists in the structure of export patterns. The findings derived from the analyses further suggest that the existence of geographical export market diversification of Sri Lanka has long run relationship with export performance.